Business Innovation of Flashbox in Digital Mental Health Startups - Handoko, Mahardika Maulana Al Mahdi; Rabbani, Muhammad Fathi (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the rapidly evolving digital era, digital mental health startups have become a crucial focus in providing accessible and efficient mental health services. This study investigates the business innovations made by Flashbox, a digital mental health startup, in creating significant impact in the mental health sector. Using both qualitative and quantitative approaches, this research delves into how Flashbox integrates cutting-edge technologies such as artificial intelligence and big data analytics to provide personalized and responsive services. The findings reveal that Flashbox has successfully implemented a sustainable business model through a user-centric approach, continuous service innovation, and effective marketing strategies. Additionally, this study also explores the challenges and opportunities faced by Flashbox in terms of scaling and regulation. These findings offer important insights for practitioners and policymakers in understanding the potential and dynamics of digital mental health startups in delivering better mental health services.